Integration of high velocity elastic band for hamstring training in pre-season routine of football players - Januševicius, D.; Snieckus, A.; Mickevicius, M.; Satkunskiene, D.; Muanjai, P.; Kamandulis, S. (Baltic Journal of Sport and Health Sciences, 2020)
Background. A need for other methods of hamstring strengthening are thus warranted with the main aim of reducing the risk of injury during the subsequent intense athletic activities. The study aimed to examine changes in hamstring strength in response to high velocity elastic band training when incorporated into regular training routine of football players.